Direct Germline Transformation of Cotton Meristem Explants With No Selection - Chen, Yurong; Lange, Andrea; Vaghchhipawala, Zarir; Ye, Xudong; Saltarikos, Annie (Frontiers in Plant Science, 2020)
Regeneration of transgenic plants without selectable markers can facilitate the development and commercialization of trait stacking products. A wide range of strategies have been developed to eliminate selectable markers to produce marker-free transgenic plants. The most widely used marker free approach is probably the Agrobacterium-based 2T strategy where the gene-of-interest (GOI) and selectable marker gene are delivered from independent T-DNAs. The selectable marker gene is to segregate away from the GOI in subsequent generations. However, the efficiency of this 2T system is much less than the traditional 1T-DNA system due to the inefficiency of T-DNA co-transformation and high rate of linkage between the GOI and selectable marker gene. In contrast, no selection transformation utilizes a single T-DNA carrying the GOI and eliminates the need to remove a selectable marker and consequently provides a viable alternative marker-free system. In this study, we reported the successful regeneration of transgenic cotton plants through Agrobacterium inoculation of seed meristem explants with no selective agents in tissue culture medium. Regeneration of putative transgenic plants were identified by GUS histo-chemical assay. The germline transmission of transgene to progeny was determined by segregation of pollen grains, immature embryos and R1 plants by GUS expression. The results were further confirmed by Southern analyses. The marker-free transformation frequency in this no selection system was similar to current meristem transformation system with selection. The strategy for further improvement of this system and its implication in improving cotton transformation pipeline and reducing the cost of transgenic plant production and in developing transgene-free genome editing technology is discussed